FAKTOR-FAKTOR YANG MEMPREDIKSI PROGNOSIS PASIEN ICH BATANG OTAK PRIMER DI RSUD CILEUNGSI TAHUN 2020 - Namira Khairunnisa (2021)
Primary brainstem hemorrhage is a infrequent type of hemorrhagic stroke but the reported mortality rate is very high. The purpose of this study is to find out the mortality rate and predictor factors that can predict the prognosis of primary brainstem hemorrhage patients. This study used a cross sectional design. Samples obtained from medical and radiological records using a total sampling technique. From January 2018 to August 2020, 340 patients were diagnosed with hemorrhagic stroke. Of the 340 hemorrhagic stroke patients, 10 patients met the inclusion criteria to be the study sample. Data analysis used the Spearman correlation test adjusted for each variable. Through the result of the study it can be concluded that prevalence of brainstem hemorrhage is 7%. Bivariate analysis showed a correlation between GCS score (P=0,005), brainstem hemorrhage location (P=0,010), and length of stay (P=0,035) towards the patient's prognosis at discharge. The management of brainstem hemorrhage should be a major focus because of the high mortality rate.